Qualitative research topics in language teacher education - Barkhuizen, Gary Patrick (New York, NY ; Abingdon, Oxon : Routledge, 2019)
"Many students and novice researchers may have a general idea of a topic they would like to research, but have a difficult time settling on a more specific topic and associated research questions. Addressing this problem, this book features contributions from over thirty diverse and experienced research supervisors, mentors, and principle investigators in the field of language teacher education. The chapters are autobiographic in nature, with each contributing author reflecting on relevant, current and innovative research topics through the lens of their own professional life and research work. Offering explicit research topics and strategies for each area of expertise, this book will serve as a useful reference for the seasoned qualitative or narrative research practitioner, and a helpful guide for the new researcher narrowing down their own research topics"--
Introduction : qualitative research topics in language teacher education / Gary Barkhuizen -- Working with doctoral dissertation writers / Christine Pearson Casanave -- Going beyond familiarity and doing the opposite in language teacher education / Tan Bee Tin -- Learning to teach languages / Donald Freeman -- Researching language ideologies / Carolyn McKinney -- Language teachers' professional learning in China / Wen Qiufang -- The impact of language teacher professional development / Simon Borg -- Language teacher psychology research / Sarah Mercer -- Emotions in language teacher education and practice / Elizabeth R. Miller and Christina Gkonou -- Researching emotion in LTE / Matthew T. Prior -- Beliefs and emotions in language teaching and learning / Ana Maria F. Barcelos -- Language teacher identities in teacher education / Bonny Norton and Peter De Costa -- Understanding language teacher identities : conceptualizations, practices and change / Maria Ruohotie-Lyhty -- Researching LTE through a Vygostkian sociocultural theoretical perspective / Paula R. Golombek -- Context in sociocultural theory / Anne Feryok -- Academic writing : linking writers, readers and text content / Rosemary Wette -- English L2 writing in international higher education / Jim McKinley -- Academic writing : the human side / Pat Strauss -- Critical questions in English for academic purposes / Gregory Hadley -- Race in critical research / Ryuko Kubota -- Gender and LTE / Harold Castañeda-Peña -- Researching English as an international language / Heath Rose -- Multilingualism in (foreign) language teaching and learning / Anne Pitkänen-Huhta -- English language teaching in multilingual contexts / Christa van der Walt -- Social representations of multilingualism / Alice Chik and Sílvia Melo-Pfeifer -- Language teacher education in study abroad contexts / John L. Plews -- Study abroad for language teachers / John Macalister -- Generating action research topics / Anne Burns -- Researching teacher research / Daniel Xerri -- Teacher researchers / Kenan Dikilitas -- Exploring issues in language and content instruction / Sandra Zappa-Hollman and Patricia A. Duff -- LTE in primary and secondary schools / Takaaki Hiratsuka -- Researching task-based teaching and assessment / Martin East -- Language teaching approaches / Jessie S. Barrot -- Strategy instruction / Carol Griffiths.
Includes bibliographical references and index.
ENH
Hye Trade International
Keywords: Language teachers -- Training of -- Research; Language and languages -- Study and teaching -- Research; Qualitative research